Bacterial Reduction after Gutta-Percha Removal with Single vs. Multiple Instrument Systems - Xavier, Felipe; Nevares, Giselle; Gominho, Luciana; Rodrigues, Renata; Kaline Romeiro, Marcelly Cassimiro; Romeiro, Kaline (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to evaluate the effectiveness of a reciprocating single-instrument system (Reciproc-REC) compared with combined continuously rotating multiple-instrument systems [D-Race (DR) and BioRace (BR)] in reducing Enterococcus faecalis (E.f.) after gutta-percha removal. Methods and Materials: Forty-six extracted human maxillary incisors were prepared and contaminated with E.f. strain (ATCC 29212) for 30 days. The samples were obturated and randomly divided into two experimental groups for gutta-percha removal (n=23): a REC group (R50) and a DR/BR group (DR1, DR2 and BR6). A standardized irrigation with 0.9% saline solution was performed. Root canal samples were taken with paper points before (S1) and after (S2) the removal of gutta-percha to establish bacterial quantification by culture. The time required for gutta-percha removal was also recorded. Positive and negative control groups (n=6) were used to test bacterial viability and control asepsis, respectively. Data were analysed using t-Student and one-way ANOVA tests (5% margin of error). Results: The mean percentage of bacterial reduction was significantly higher in DR/BR group (84.2%) than in REC group (72.3%) (P<0.05). The mean time for obturation removal was 74.00 sec in REC group and 107.53 sec in DR/BR group (P<0.05). Conclusion: The combined continuously rotating multiple-instrument system was more effective in reducing bacteria after the removal of gutta-percha than the single-instrument system. None of the tested systems was able to completely eliminate root canal infection after gutta-percha removal. Thus, additional techniques should be considered. Keywords: Endodontics; Enterococcus faecalis; Instrumentation; Retreatment; Root Canal Instrumentation